The Accuracy of Bankruptcy Prediction using Z-Score and Springate in Tourism and Recreation Industry - Claresta Khenisa Putri; Gerianta Wirawan Yasa (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
Every company has the potential to experience bankruptcy. Bankruptcy can be predicted by using accurate bankruptcy prediction model. The purpose of this study is to compare which model is more effective between the Altman Z-Score and the Springate model in predicting bankruptcy. The data used in this research is secondary data in the form of financial statements of Tourism and Recreation Industry companies listed on the Indonesia Stock Exchange during the 2020-2022 period. The sample consist of 41 companies selected using purposive sampling. The data is analyzed using Mann-Whitney test. The result of this study indicates the accuracy of Z-Score model is higher compared to Springate model. The research also shows a significant difference between Z-Score and Springate. These findings imply that the Z-Score model is more effective for predicting bankruptcy in the Tourism and Recreation Industry compared to the Springate model.